Recording daily routines with guidance on healthy lifestyle to improve health parameters in children and their families - Raiane Maiara dos Santos Pereira; Suliane Beatriz Rauber; Isabela Almeida Ramos; Daniel Tavares de Andrade; Angeliete Garcez Militão; José Fernando Vila Nova de Moraes; Herbert Gustavo Simões; Carmen Sílvia Grubert Campbell
Abstract This study investigated the efficacy of using a diary to record daily routines, combined with guidance on healthy lifestyle (GHL) by a physical educator, on promoting changes in health parameters in children. Sixty-three children (10 ± 0.8 years) were allocated to one of the three following groups: a control group (CON, n = 18); a group that did not use the diary, but received GHL (G, n = 23); or a group that both used the diary and received GHL (DG, n = 22). Blood pressure, body composition, physical fitness tests (PF), physical activity levels (PAL), and dietary intake profiles were assessed in children and their parents before and after 2 months of intervention. The DG group improved their performance in PF, increased PAL, and reduced body fat (p < 0.05). Additionally, 56% of families from both DG and G reduced their consumption of unhealthy foods and 70,6% increased their consumption of healthy foods. Overall, it was concluded that 2 months of using a diary to record daily routines combined with GHL by a physical educator improved PAL, PF, body composition, and dietary intake profiles of children and their families.